A dual-layer micro/nanostructured fibrous membrane with enhanced ionic conductivity for lithium-ion battery. (1st December 2018) - Chen, Yifan; Gao, Yue; Jian, Jiejie; Lu, Yihan; Zhang, Bingying; Liu, Haiqing; Li, Lei; Wang, Xiangwei; Kuang, Chunxia; Zhai, Yunyun
Abstract: Electrospun fiber-based composite membrane with interconnected porous structure has drawn significant attention for application in lithium-ion battery (LIB) owing to its high ion transportation. Here, we report a facile approach to fabricate the hierarchically micro/nanostructured ultrathin SiO2 -PAN skin layer on the PAN-PU fibrous membrane surface via electrospinning and sequential electrospraying techniques. Benefiting from the synergistic effect of the micro/nanostructure and the superior electrolyte affinity of the SiO2 -PAN skin layer, the as-prepared SiO2 -PAN@PAN-PU membrane demonstrates the decreased pore size (1.18 μm), enhanced ionic conductivity (1.4 mS cm −1 ) and robust electrochemical stability up to 5.08 V. Moreover, the introduction of skin layer endows the as-prepared SiO2 -PAN@PAN-PU membrane with improved stress strength (15.7 MPa) and excellent thermostability of 200 °C. Compared with the PAN-PU and Celgard membranes, the dual-layer micro/nanostructured SiO2 -PAN@PAN-PU fibrous membrane based Li/LiFePO4 cell assembled with high mass-loading LiFePO4 demonstrates a more stable cycling lifetime with a high discharge capacity (107.4 mAh g −1 at the 105th cycles) and higher rate capability (75.2 mAh g −1 at 1 C). The strategy using electrospraying technique demonstrated in this work will open the door to narrow fibrous membrane pore size and enhance ionic conductivity for potential application in the high-power LIB. Graphical abstract: Highlights: Introduction of SiO2 -PAN decreased pore size & possibility of internal shorting. Synergetic effect of SiO2, PAN, PU improved ionic conductivity and thermostability. A facile way to tune pore structure of electrospun nanofibers was proposed. SiO2 -PAN@PAN-PU nanofibers based cell exhibited high stability and rate capability.